Critical review of nuclear power plant carbon emissions - Liu, Bojie; Peng, Binbin; Lu, Fei; Hu, Jiang; Zheng, Li; Bo, Meifang; Shang, Xin; Liu, Weiwei; Zhang, Yichi; Zhou, Xiafei; Jia, Pengfei; Liu, Gengyuan (Frontiers in Energy Research, 2023)
Nuclear power plays a crucial role in achieving the target of carbon neutrality to build a sustainable society. However, it is not “carbon-free” when considering its entire life cycle. Therefore, accurate accounting and monitoring of its generated carbon emissions are required to avoid miscalculations of nuclear energy as a clean energy source. In this study, the life-cycle carbon emissions of nuclear power plants (NPPs) with different reactor types are reviewed. In addition to the characteristic differences among different reactors, disparities in the review results originate from the varying emissions at the respective stages of the nuclear fuel cycle, technology choices at each stage and accounting methods and boundaries. The carbon emissions resulting from NPP construction and operation are underestimated due to the limited data and methods, which creates uncertainty in the evaluation of NPP carbon emissions. An integrated framework for carbon emissions accounting considering the construction and operation of NPPs (CACO-NPP) is proposed. This integrated framework aims to improve the accounting accuracy for carbon emissions originating from NPPs. An emerging Generation III NPP with the latest technology, HPR1000 (an advanced pressurized water reactor), was adopted as a case study. The results show that the total emissions resulting from vegetation loss, equipment manufacturing and labor input during construction and operation are 1232.91 Gg CO2 with a carbon intensity of 1.31 g CO2/kWh, indicating the notable mitigation capability of Generation III NPPs. By combining the maturity of HPR1000 technology with successive design improvements, the carbon emissions of such reactor types could be further reduced. This development is very important for realizing China’s carbon neutrality target.